Effect of the growing features on luminescence and thermal glow of CdWO₄ scintillation crystals - Luchechko, A.P.; Zakharko, Ya.M.; Solsky, I.M.; Pashkovsky, M.V.; Zorenko, Yu.V. (Functional Materials, 2005)
Investigation results of absorption, X-ray-, photo-, and thermally stimulated luminescence spectra of CdWO₄ crystals are presented as depending on the growing features thereof. Essential changes in relative intensity of some emission bands under X-ray and N₂-laser excitation have been observed. The raw material purification in the course of the preliminary recrystallization has been shown to result in an enhanced X-ray luminescence intensity in the blue-green spectral region and in decreased thermal glow peaks responsible for the slow luminescence components.